Effect of Different Nitrogen and Potassium Rates on Agronomic Characters of Aloe indica - Kazi Liaquat Hossain; Md. Abdul Wadud; Md. Abul Kashem; Edi Santosa; Md. Shajahan Ali (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2007)
A field study was conducted to investigate the growth of Aloe indica with different rates of nitrogen and potassium fertilizers at the Germplasm Centre, Department of Horticulture, Bangladesh Agricultural University.  Treatments consisted of 0, 200 and 300 kg nitrogen/ha and 0, 100 and 200 kg potassium/ha. The rates of nitrogen and potassium had significant effect on the leaf production of Aloe indica when compared to control. Leaf yield of Aloe indica was highest at application of nitrogen at rate 200 kg/ha and potassium at rate 100 kg/ha. Leaf protein content was 12.71% higher at 200 kg N/ha and 8.47% higher at 300 kg N/ha compared to control. Potassium application at rate of 100 and 200 kg/ha produced 4.86 % and 8.51% higher leaf protein content than the control, respectively. It is recommended to apply nitrogen at rate 200 kg/ha and potassium at rate 100 kg/ha for leaf production of Aloe indica.   Key words: Aloe indica, chemical fertilizers, leaf nitrogen, protein content, potassium content